[Nesting of Golden Eagle (Aquila chrysaetos) at an exceptional altitude for the Italian Alps] - Fabiano Sartirana; Rudy Valfiorito (Rivista Italiana di Ornitologia - Research in Ornithology, 2019)
[In the Province of Imperia (Liguria, Italy) the breeding population of Golden Eagle (Aquila chrysaetos) amounts to 8 territorial pairs, with a relative density of 4.6 pairs/1000 km2. Between the 12 known nesting sites, one nest is located at 380 m a.s.l.; this altitude might be regarded the lowest of the Prealps and Italian Alps. The local pair nested successfully in recent years.]